Offshoring, inward investment and export performance in Ireland - Frank Barry; Adele Bergin (The Economic and Social Research Institute (ESRI), 2012)
Ireland is one of the most FDI-intensive economies in the OECD and is a significant export platform for both manufacturing and internationally traded services. This chapter provides case studies of three of the most important FDI-intensive manufacturing sectors - ICT, pharmaceuticals and medical devices - and two of the substantially foreign-owned internationally traded services segments - software & IT and international financial services. It also updates earlier analyses of how Ireland's inward FDI sectors have fared over the course of the global financial crisis.
Keywords: 330; Auslandsinvestition; Ausländisch; Auslandsverlagerung; Industrie; Dienstleistungssektor; Multinationales Unternehmen; Export; Irland